Understanding barriers and opportunities for adoption of conservation practices on rented farmland in the US. (January 2019) - Ranjan, Pranay; Wardropper, Chloe B.; Eanes, Francis R.; Reddy, Sheila M.W.; Harden, Seth C.; Masuda, Yuta J.; Prokopy, Linda S.
Highlights: Landowners and farmers of rented farmland face several barriers to conservation. Some of these barriers are unique to the role of the landowner or farmer. Improving communication and sharing of risks/rewards are important. Conservation programs should continue to offer communication & lease tools. Abstract: Agricultural conservation programs often focus on farm operators when promoting conservation practices. However, much of U.S. farmland is owned by landowners not directly involved in farm operations. Rental arrangements on these lands can dis-incentivize the adoption of conservation practices that could improve soil health, water quality, and land values. To date, agricultural conservation policy has largely ignored the role of non-operating landowners (NOLs) and rental arrangements. We help improve the evidence-base for policy by identifying barriers to adoption of conservation practices on rented farmlands. Analysis of forty interviews with NOLs, operators, farm managers and university extension personnel in Iowa, Illinois, and Indiana revealed five categories of barriers: cash rent lease terms, rental market dynamics, information deficits/asymmetries, cognitive/interpersonal, and financial motivations. Some barriers, such as risk aversion and farm aesthetics were expressed by both NOLs and operators, while other barriers, such as status quo bias and annual renewal of leases were only expressed by NOLs and operators, respectively. To overcome barriers to conservation, interviewees recommended improving communication between NOLs and operators and modifying cash rent lease terms in order to build in flexibility for equitable sharing of risks and rewards. Agricultural conservation programs could readily apply these results—possibly working with intermediaries (e.g., farm managers, lawyers)—to offer communication and lease tools and assistance to NOLS and operators. Future research should evaluate the efficacy of these conservation interventions and how intermediaries affect the balance of power between NOLs and operators.